(untitled) (Journal of Engineering, 2023)
This manuscript investigated the effect of anchorage CFRP wrapping sheets, bolts, and laminate interlock on increasing the efficiency of flexural strengthening for the post-tension girder using CFRP composites techniques longitudinal laminates at the soffit for partially damaged loss of about 14.3% from its area of prestressed concrete beams, and the impact on restoring the original flexural capacity of PC girder. Mitigating delamination of the soffit of horizontal laminates (CFRP). The texture of the laminate and anchorages influenced the stress of the laminate carbon fiber, the mode of crack propagation and failure, and consequently, the beam’s attitude has been investigated in this manuscript. The experimental findings demonstrated that using CFRP laminates significantly affects strand strain, especially when anchorage wrapping is applied. The laminates CFRP-EB enhanced the flexural capacity by around 13% of the original strength, which equates to a 13% increase in strand damage. Despite an increase in flexural capacity of 20%, 22%, and 29% when using anchorage wrapping, mechanical bolts, and laminate interlock, respectively. It has been proposed to use quasi-experimental equations to predicate the actual stress of un-grouted strands, considering the influence of CFRP laminate and wrapping anchorage sheets techniques only. The experiment outcomes demonstrated that using Anchored CFRP significantly affects load-carrying capacity and cracking load by up to 29% and delays the bonding failure.